EVALUASI PENATAUSAHAAN ASET PADA PEMERINTAH KABUPTEN SARM - Mutmainnah HS Dimo; Syaikhul Falah; Arius Kambu (Universitas Cenderawasih, 2020)
The research objective was to evaluate the administration of regional property in the Sarmi Regency Government. The administrative aspects that were studied included the aspects of bookkeeping, inventory and reporting. Qualitative and quantitative methods are used to answer the research formulation. The research object consisted of three Regional Apparatus Organizations (OPD), including the Public Works Office, the Health Office and the Education Office. The interviewed informants are treasurers of goods. The interviewed informants were managers of regional property in three regional apparatus organizationsThe results of the research show that the Sarmi Regency Government has not fully implemented asset administration in accordance with the Minister of Home Affairs Regulation No. 19 of 2016. It is the only aspect of bookkeeping that has the highest value or has implemented regulations. Furthermore, the reporting and inventory aspects have not been said to have carried out regulatory orders.The results of this research resulted in the findings of several obstacles, namely: misuse of assets, weak coordination, lack of human resources to handle assets, and limited incentives for asset managers.